2023
DOI: 10.1007/s11103-023-01369-x
|View full text |Cite
|
Sign up to set email alerts
|

miR397-LACs mediated cadmium stress tolerance in Arabidopsis thaliana

Abstract: Cadmium (Cd) is a non-essential heavy metal, assimilated in plant tissue with other nutrients, disturbing the ions' homeostasis in plants. The plant develops different mechanisms to tolerate the hazardous environmental effects of Cd. Recently studies found different miRNAs that are involved in Cd stress. In the current study, miR397 mutant lines were constructed to explore the molecular mechanisms of miR397 underlying Cd tolerance. Compared with the genetically modi ed line of overexpressed miR397 (arti cial m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Cadmium is a particularly persistent trace metal and a hazardous environmental pollutant [47] that is not essential for key plant metabolic or growth processes [48]. Therefore, Ali et al constructed Arabidopsis thaliana miR397 mutant lines to investigate the molecular mechanisms responsible for the potential relationship between cadmium tolerance and miR397 expression [49]. They found that overexpressing miR397 alters lignin content and reduces cadmium tolerance by regulating laccase 2, 4, and 17 expressions.…”
Section: Mirnas and Heavy Metal Stressmentioning
confidence: 99%
“…Cadmium is a particularly persistent trace metal and a hazardous environmental pollutant [47] that is not essential for key plant metabolic or growth processes [48]. Therefore, Ali et al constructed Arabidopsis thaliana miR397 mutant lines to investigate the molecular mechanisms responsible for the potential relationship between cadmium tolerance and miR397 expression [49]. They found that overexpressing miR397 alters lignin content and reduces cadmium tolerance by regulating laccase 2, 4, and 17 expressions.…”
Section: Mirnas and Heavy Metal Stressmentioning
confidence: 99%